Rekomendasi Pemilihan Program Studi Menggunakan Algoritma Naïve Bayes - Hamzah Nurrifqi Fakhri Fikrillah; Dede Kurniadi (Institut Teknologi Garut, 2023)
The purpose of this study is to provide recommendations for selecting study programs for prospective students who will enter the Garut Institute of Technology (ITG). The results of this recommendation will provide information on study programs that are in accordance with the academic value of the prospective student. To achieve this goal, this study uses the Naïve Bayes Algorithm to predict future opportunities based on past data, then to get recommendation results by finding the greatest probability value for each attribute. The stages of the algorithm carried out include data collection, data processing, modeling, and evaluation. The data used for analysis needs to use data that corresponds to the Final Grades of Garut College of Technology students during their school years from 2014 to 2019 with a total of 30 data in each study program with a total of 90 data. From the four modeling times data and algorithm testing resulted in the best Naïve Bayes algorithm calculation accuracy with an accuracy of 73.4%.